Innate Responses to Aspergillus: Role of C1q and Pentraxin 3 in Nasal Polyposis - Baruah, Paramita; Trimarchi, Matteo; Dumitriu, Ingrid E.; Dell'Antonio, Giacomo; Doglioni, Claudio; Rovere-Querini, Patrizia; Bussi, Mario; Manfredi, Angelo A. (American journal of rhinology, 2007)
Background Pentraxin 3 (PTX3) and complement component C1q are humoral factors of innate immunity, produced at sites of inflammation, and are essential in immune defense against several microbes such as Aspergillus, which is commonly implicated in nasal polyposis. Methods PTX3 and C1q were measured in nasal polyp tissue, normal nasal mucosa, and serum of patients and healthy subjects. Immunohistochemistry for the two proteins was done on normal nasal mucosa and nasal polyps. In addition, PTX3 and C1q production from mononuclear cells from patients and healthy subjects was assessed. Results Normal nasal mucosa was found to have 100-fold higher levels of PTX3 compared with serum. No measurable local increase of PTX3 was observed in polyps compared with normal mucosa. Immunohistochemistry revealed PTX3 expression in the lining of blood vessels both within normal mucosa and nasal polyps. PTX3 also was present in mononuclear cells infiltrating nasal polyps. C1q levels were higher in polyps than in normal nasal mucosa. Conclusion High levels of PTX3 are present in normal nasal mucosa, suggesting a role in the maintenance of tissue homeostasis. Elevated C1q levels in nasal polyps might be indicative of an ongoing inflammatory response in the nasal mucosa in these patients.